5.7k views
3 votes
19(2m−16)=13(2m+4) (pls helppp)

1 Answer

6 votes

Answer:

Simplified this is -304 + 38m = 52 + 26m

m in the equation is 29 2/3

Explanation:

Reorder the terms:

19(-16 + 2m) = 13(2m + 4)

(-16 * 19 + 2m * 19) = 13(2m + 4)

(-304 + 38m) = 13(2m + 4)

Reorder the terms:

-304 + 38m = 13(4 + 2m)

-304 + 38m = (4 * 13 + 2m * 13)

-304 + 38m = (52 + 26m)

Simplfied answer:

-304 + 38m = 52 + 26m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-26m' to each side of the equation.

-304 + 38m + -26m = 52 + 26m + -26m

Combine like terms: 38m + -26m = 12m

-304 + 12m = 52 + 26m + -26m

Combine like terms: 26m + -26m = 0

-304 + 12m = 52 + 0

-304 + 12m = 52

Add '304' to each side of the equation.

-304 + 304 + 12m = 52 + 304

Combine like terms: -304 + 304 = 0

0 + 12m = 52 + 304

12m = 52 + 304

Combine like terms: 52 + 304 = 356

12m = 356

Divide each side by '12'.

m = 29.66666667

Simplifying

m = 29.66666667 = 29 2/3

User Sombir Kumar
by
6.2k points